Assessing African economic responses to COVID-19 - Tadesse, Getaw; Tefera, Wondwosen (AKADEMIYA2063, 2021)
In early 2020, African governments adopted a wide range of containment and confinement measures to limit the spread of COVID-19 in the continent. The measures included border closures, suspension of international flights, closures of markets and schools, state-of-emergency declarations, total and partial lockdowns, restrictions on internal movement, imposition of curfews, and closures of nonessential businesses (UN-Habitat 2020; IMF 2020). To mitigate the adverse economic effects of these health measures, governments implemented various emergency economic supports and regulations. Several institutions have tracked the type and size of responses by African countries to ease the adverse impacts on agricultural development, food security, finance, and trade (Laborde and Parent 2020; Bisson and Hambleton 2020). These studies have explored the incidence and impacts of emergency responses with the objective of estimating the costs of COVID-19. Similarly, AKADEMIYA2063 has established analytical workstreams to monitor the impacts of COVID-19 on food production, markets, trade, and households (Badiane and Collins 2020). However, these studies have evaluated the overall impact of COVID-19 without disentangling the impacts of the health measures from those of the economic measures.